E-COMMERCE PAYMENT AUTHENTICATION SYSTEM WITH SIM CARD - Tanaya, Rico Andropurnomo (Jurnal Sistem Komputer, 2017)
Smart card is a device, which used for multi purpose needs to secure content and information. This device has many forms, for example like cards, which used to secure banking transaction, SIM card, which used to store operator subscriber’s information as well as embedded smart card which used for many IOT (Internet Of Things) devices. The purpose of this research is to test whether SIM card can be used to secure credit card data that besides to store data, SIM card can also used to do verification and encryption. This research uses multiple standardizations as a base to build the prototype simulation that is PA-DSS and ISO 7816. PA-DSS standard used as a base to build client side and server side application and ISO 7816 is a protocol interface for smart card. With this research, I hope that we can see clear that it is possible to build a alternate payment system by using SIM card for storing purpose and credit card verification.